Výsledky léčení zlomeniny patní kosti LCP dlahou s augmentací a bez augmentace - Zeman, Jaroslav; Matějka, Tomáš; Zeman, Petr; Belatka, Jaroslav; Matějka, Jiří (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2019)
PURPOSE OF THE STUDY The retrospective study aims to compare the outcomes of augmentation of neutral triangle formed after the calcaneal fracture reduction with osteosynthesis using the locking compression plate with the outcomes of osteosynthesis without augmentation. MATERIAL AND METHODS In the period from 2005 to January 2011, 98 patients with 114 calcaneal fractures were treated by open reduction and internal fixation (ORIF) method with the use of calcaneal plate. The group included 15 women (15.3%) and 83 men (84.7%), with the mean age of 39.2 years (12-62 years). There were 16 cases of bilateral calcaneal fractures, of which 2 in women (12.5%) and 14 in men (87.5%). The fractures were classified based on the Sanders classification as Type I -IV. The patients with Type II and III fracture according to the Sanders classification were indicated for surgical treatment with ORIF using the calcaneal LCP. The defect in the region of neutral triangle of the calcaneus was filled with the injectable hydroxyapatite cement. The cohort of operated patients was evaluated based on the AOFAS (American Orthopaedic Foot and Ankle Society) Clinical Rating System. The bilateral fractures were not evaluated. This group shows a substantially higher occurrence of associated injuries, which causes strong distortion of results. RESULTS The cohort of 82 operated patients with Sanders Type II and III fractures were evaluated. In 20 fractures (24.4%) the defect in the calcaneus body was filled with hydroxyapatite cement. In osteosynthesis without defect augmentation an excellent result was achieved in 21 patients (33.9%). A good result was reported in 24 patients (38.7%), a satisfactory result in 12 patients (19.4%) and a poor result in 5 patients (8.0%). In patients with osteosynthesis of the calcaneus with augmentation, an excellent result was achieved in 6 cases (30%), a good result in 5 cases (25%), a satisfactory result in 7 cases (35%) and a poor result in 2 cases (10%). Early postoperative complications were observed in a total of 13 patients (15.8%). In osteosynthesis without defect augmentation, there were 2 cases of wound dehiscence (3.2%), 3 cases of marginal skin necrosis (4.8%), 4 cases of superficial wound infection (6.4%) and 1 case of deep wound infection (1.6%). In patients with performed augmentation, wound dehiscence was seen in 1 case (5%), superficial wound infection in 1 case (5%) and superficial marginal skin necrosis in 1 case (5%). Deep wound infection was not reported in this group. DISCUSSION A question frequently discussed is the filling of defect in the diaphysis of calcaneus. Brodt et al. state a statistically higher stability of the calcaneus in osteosynthesis with augmentation, but he does not use the locking plate. Longino in his study compares the results of calcaneal osteosynthesis with spongioplasty with a graft from pelvis and without it and does not observe any major differences in the final outcome in his cohort. Elsner evaluates the results in 18 patients, in whom calcium phosphate cement augmentation was used for osteosynthesis. Over the period of three years he did not observe a higher rate of complications. Schildhauer assesses the early load of the calcaneus with tricalcium phosphate cement augmentation. After three weeks of full loading no loss of reduction was found. Thordarson evaluates 11 operated patients with Sanders type II and III calcaneal fracture. The defect of the calcaneus was filled by calcium phosphate cement. In this small group 1 case of serious infection complication and 1 loss of reduction with full load at six weeks after the surgery were observed. In our group no differences were observed between the outcomes of patients with performed or not performed defect augmentation in the neutral triangle site. A higher percentage of complications in patients with filled defect of the calcaneus was not observed either. CONCLUSIONS The operative treatment of displaced intra-articular fractures consisting of open reduction from extended lateral approach and internal calcaneal LCP fixation brings good results. We concluded that there is no statistically significant difference in the results of osteosynthesis with a locking plate alone and combined with augmentation of diaphyseal defect of the calcaneus. Filling of the diaphyseal defect in the calcaneus is not necessary, it neither accelerates the healing, nor brings better treatment outcomes Key words: calcaneal fracture, cement augmentation of defect, locking plate, extended lateral approach.
Keywords: Calcaneus; dospělí; fraktury kostí; Female; dítě; Adult; výsledek terapie; mladý dospělý; ženské pohlaví; Adolescent; lidé; Fractures, Bone; Treatment Outcome; patní kost; retrospektivní studie; Bone Plates; kostní destičky; Male; Young Adult; vnitřní fixace fraktury; lidé středního věku; Child; mužské pohlaví; Retrospective Studies; Middle Aged; mladiství; Fracture Fixation, Internal; Humans